Profiling Students’ Interest in Mathematics Learning in a Conventional Classroom Context - Fitria Dwi Khaerunnisa; Indra Budiman (Jurnal Didactical Mathematics, 2026)
Students’ interest in learning mathematics plays an important role in shaping engagement and participation during classroom instruction. However, in many classroom settings, students’ interest in mathematics learning remains limited despite regular participation in instructional activities. This study aimed to examine the empirical profile of students’ interest in learning mathematics in a conventional classroom context. A descriptive quantitative research design was employed to analyze students’ learning interest using four indicators: enjoyment of learning mathematics, attention to instructional materials, attraction to the subject, and participation in classroom learning activities. Data were collected through a structured questionnaire administered to 30 seventh-grade students in a junior secondary school. The results indicate that students’ learning interest remained relatively low across all measured indicators. Although attention toward instructional materials showed slightly higher values than the other indicators, the levels of enjoyment, attraction to mathematics, and classroom participation were consistently low. These findings reveal a noticeable gap between students’ attentiveness during instruction and their broader affective engagement with mathematics learning. The study provides an empirical description of students’ interest in learning mathematics within a conventional instructional environment and offers insight into how classroom learning conditions relate to students’ affective engagement in mathematical learning activities